2020
DOI: 10.1177/2325967120905022
|View full text |Cite
|
Sign up to set email alerts
|

Modified Weaver-Dunn Procedure for Type 3 Acromioclavicular Joint Dislocation: Functional and Radiological Outcomes

Abstract: Background Controversy surrounds the indication for treatment of type 3 acromioclavicular joint dislocation, and the optimal reconstructive technique has not yet been defined. Since the first description of the Weaver-Dunn procedure, several studies have described the clinical and radiological results that can be expected postoperatively; however, few studies have evaluated the outcomes of this technique for chronic type 3 acromioclavicular joint dislocation. Purpose/Hypothesis The purpose of this study was to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 35 publications
0
9
1
Order By: Relevance
“…Both the WD procedure and the CCR procedure achieved satisfactory outcomes in terms of treating chronic AC dislocations [2,23,30,31]. Some studies supported the use of the WD procedure [14,15,[30][31][32] whereas others favored CCR techniques [2,5,6,23]. A meta-analysis was further conducted to compare the outcomes for the WD procedure and CCR in the treatment of chronic AC dislocations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both the WD procedure and the CCR procedure achieved satisfactory outcomes in terms of treating chronic AC dislocations [2,23,30,31]. Some studies supported the use of the WD procedure [14,15,[30][31][32] whereas others favored CCR techniques [2,5,6,23]. A meta-analysis was further conducted to compare the outcomes for the WD procedure and CCR in the treatment of chronic AC dislocations.…”
Section: Discussionmentioning
confidence: 99%
“…The original WD procedure included a lateral clavicle resection, reduction of the dislocated clavicle, and transfer of the coracoacromial ligament to the lateral clavicle without additional fixation [33]. Later, numerous studies discussed modified WD procedures using various additional fixation devices intended to provide further stability and maintain reduction of the AC joint, in which satisfactory clinical and radiological outcomes were achieved [32,[34][35][36]. One study reported that 75% of the modified WD procedures had good to excellent results [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…11 More than 60 techniques have been described in the literature for CC reconstruction in the setting of AC joint injuries, including many variations in the mWD. 9,12 In a systematic review focused solely on AC and CC ligament reconstruction, Moastshe et al looked at 939 patients in 34 studies. Interventions included free tendon graft, suspensory devices, synthetic ligaments, mWD, and hook plate.…”
Section: Discussionmentioning
confidence: 99%
“…Type 3 injuries are initially treated conservatively. Surgical intervention is done if needed later on [12][13][14].…”
Section: Discussionmentioning
confidence: 99%